ANALISIS PENGARUH HARGA, PROMOSI DAN GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN PADA TIKET.COM - Frista Giovinda (2020)
This study uses quantitative descriptive methods conducted on respondents who have made purchases at Tiket.com. the purpose of this study was to determine whether price, promotion and lifestyle influence purchasing decisions. Tiket.com is a company that has a focus on a web and application with online booking and ticketing features that provide ticket reservation services. The population in this study is Tiket.com users who live in West Jakarta, aged 20-30 and have bought or booked tickets at Tiket.com. Samples taken as many as 75 respondents using purposive sampling method through the distribution of questionnaires with Google Form. The analysis technique used is descriptive analysis and inferential analysis and the analytical tool in this study is partial Least Square (PLS). The results of this study indicate that: (1) Price influences and is significant for purchasing decisions. (2) Promotion influences and is significant for purchasing decisions. (3) Lifestyle has no effect and is not significant on purchasing decisions. With the R-Square Adjusted generated 77.2%.